PagERF16 of Populus Promotes Lateral Root Proliferation and Sensitizes to Salt Stress - Wang, Shengji; Huang, Juanjuan; Wang, Xingdou; Fan, Yan; Liu, Qiang; Han, Youzhi (Frontiers in Plant Science, 2021)
The aggravation of soil salinization limits the growth and development of plants. The AP2/ERF transcription factors (TFs) have been identified and play essential roles in plants development and stress response processes. In this study, the function of PagERF16 was detected using the overexpressing (OX) and RNAi transgenic poplar 84K hybrids. Plant growth, stomatal conductance, antioxidant enzymes activity, as well as PagERF16 co-expressed TFs were analysed using morphological, physiological and molecular methods. OX showed a robuster lateral root system with bigger diameter and volume compared to the wild-type plants (WT). Physiological parameters indicated the bigger stomatal aperture and lower stomatal density of OX along with the lower Catalase (CAT) activity and higher malondialdehyde (MDA) content contributed to the salt sensitivity. The plant height and rooting rate of OX and RNAi were significantly worse compare to WT. However, the other morphology and physiology of RNAi were similar to WT which suggested that function of PagERF16 may be redundant with other TFs and too high or too low expression level of PagERF16 is not good for poplar growth and rooting. In addition, a downstream target TF, NAC45, involved in Auxin biosynthesis, was identified and PagERF16 could directly bind to its promoter to negatively regulate its expression, which in turn promoted lateral roots proliferation. These results will give new lights in the function of ERF TFs in plant growth and salt stress tolerance.